PREMENSTRUAL SYNDROME AND SLEEP QUALITY AMONG MEDICAL STUDENT - Gloria Fernandez; Benedictus Triagung Ruddy Prabantoro; Pauline Meryana (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: Premenstrual syndrome (PMS) is a collection of physical, psychological, and behavioral symptoms associated with a woman's menstrual cycle due to hormonal changes during ovulation and menstruation. Data on New Delhi shows that 75% of women of childbearing age experience mild to severe PMS symptoms. PMS harms social and work life, leading to psychological and mental health problems affecting sleep quality. The incidence of PMS in medical students is 90.3%.Objective: To determine the relationship between PMS and sleep quality in female students of the Faculty of Medicine, Widya Mandala Surabaya Catholic University.Methods: The method used in this study was observational-analytic, cross-sectional, and simple random sampling. Data were collected using the Shortened Premenstrual Assessment Form (SPAF) questionnaire to assess the degree of PMS and the Pittsburgh Sleep Quality Index (PSQI) questionnaire to assess sleep quality. Data were tested using Fisher Exact Test.Results: Sixty-five female students met the inclusion criteria. Students with mild PMS or without PMS had good sleep quality, 38.3%, and 61.7% had poor sleep quality. In the moderate or severe PMS group, all (100%) experienced poor sleep quality. From the statistical analysis, the result of p = 0.103 (p>0.05) means no significant relationship exists between PMS and the sleep quality of female students of the Faculty of Medicine, Widya Mandala Surabaya Catholic University.Conclusion: There is no relationship between PMS and sleep quality in female medical students.